Regional and local phenomena influencing the thermal state in the Flysch belt of the northeastern part of Slovakia - MAJCIN, Dušan; BILČÍK, Dušan; KUTAS, Roman; HLAVŇOVÁ, Petra; BEZÁK, Vladimír; KUCHARIČ, Ľudovít (Contributions to Geophysics and Geodesy, 2014)
The locality of the northeastern most part of Slovakian Flysch belt belongs to interesting areas in terms of the interpretation of geothermal conditions in mutual relation with the lithosphere structure and their tectonic development. The evaluation of the geothermal energy sources parameters of this locality is likewise worthwhile. The region under study has the centre in position of the borehole Zboj ZB-1 and spreads out Slovakia also in Poland and Ukraine. Our contribution provides the analyses of existing geothermal data enhanced by the construction of temperature field models corresponding to the global and local aspects that influence the temperature and heat flow density distributions. The analyses are related to the structures and effects of separate phenomena along as well as across the Carpathian arc. The model calculations were carried out both by analytical and numerical methods of solving the heat transfer equations including their steady state forms and transient cases too. Besides the regional trend of thermal activity decrease in direction from East-Slovakian Basin to the outer Carpathian units the combined local influences are applied: subsurface thermophysical parameters of rock complexes distributions, non-stationary sources from supposed subvolcanic bodies in close surroundings of borehole Zboj ZB-1, and the effects of the hydrological factors. Considering the observed higher thermal activity in arched zone along the Carpathian structures we discussed the thermal effects of rock complexes supposed as a source of regional Carpathian Conductivity Anomaly and the transfer of heat from East-Slovakian Basin to Outer Carpathian Flysch units. The analysis and themodelling results suggest that the mentioned activity is caused by the influences of source type phenomena mainly related to deep fault systems at the margin of the European Platform.